Dynamic thermal-hydraulic modelling of the EU DEMO HCPB breeding blanket cooling loops. (November 2016) - Froio, A.; Bachmann, C.; Cismondi, F.; Savoldi, L.; Zanino, R.
Abstract: A global, system-level thermal-hydraulic model of the EU DEMO tokamak fusion reactor is currently under development and implementation in a suitable software at Politecnico di Torino, including the relevant heat transfer and fluid dynamics phenomena, which affect the performance of the different cooling circuits and components and their integration in a consistent design. The model is based on an object-oriented approach using the Modelica language, which easily allows to preserve the high modularity required at this stage of the design. The first module of the global model will simulate the blanket cooling system and will be able to investigate different coolant options and different cooling schemes, to be adapted to the different blanket systems currently under development in the Breeding Blanket (BB) project. The paper presents the Helium-Cooled Pebble Bed (HCPB) module of the EU DEMO blanket cooling loops system model. The model is used to compare different schemes for the cooling of the different components of the HCPB BB, and to suggest improvements aimed at optimizing the pumping power required by the cooling system. The model is then used to analyse a pulsed scenario, characteristic of the EU DEMO operation. Highlights: Thermal-hydraulic model of the HCPB Breeding Blanket cooling loop developed. Model written using the Modelica language. High modularity, allowing test of different cooling options. Steady-state comparison of two different cooling schemes performed. Test in transient conditions for a nominal pulsed plasma scenario.